EXTERNAL VALIDATION OF THE MANCHESTER ACUTE CORONARY SYNDROMES (MACS) DECISION RULE. Issue 12 (23rd November 2015) - Carlton, E; Body, R; Greaves, K
Abstract : Objectives & Background: The Manchester Acute Coronary Syndromes (MACS) decision rule has been shown to be a powerful diagnostic tool in emergency department (ED) patients with suspected acute coronary syndromes (ACS). It has the potential to improve system efficiency by identifying patients suitable for discharge after a single blood draw, for high-sensitivity troponin and heart-type fatty acid binding protein analysis, at presentation to the ED. We aimed to externally validate the MACS decision rule and establish its diagnostic accuracy as a discharge tool in a new set of prospectively recruited ED patients. Methods: In this post-hoc analysis of a prospectively recruited single-centre cohort we included consecutive ED patients ≥18 years with suspected ACS. Testing for heart-type fatty acid binding protein and high-sensitivity troponin T was undertaken on serum drawn on arrival and clinical features required to calculate the MACS rule recorded. The primary outcome was major adverse cardiac events (MACE) within 30 days (acute myocardial infarction (AMI), death or revascularisation). The secondary outcome was AMI alone, adjudicated using 6 h troponin results. Results: Of the 782 participants included, 78 (10.0%) developed MACE and 61 (7.8%) had an AMI. Of participants, 133 (17.0%) were identified as 'very low risk' and therefore suitable for immediate discharge with a 0% incidence of MACE or AMI. The sensitivity was 100% (95% CI 95.4–100) for MACE at 30 days and 100% (95% CI 94.1–100) for AMI. Of the 'high risk' group, 53.3% had a MACE within 30 days (Figure 1). The area under the ROC curve was 0.87 (95% CI 0.83–0.91) for the MACS rule in the prediction of MACE (Figure 2). Conclusion: In this prospectively recruited cohort, the MACS decision rule identifies a significant proportion of patients who are suitable for immediate discharge after a single blood draw at presentation, with a 0% risk of MACE. The rapid assessment and discharge of these patients is likely to reduce healthcare resource burden and costsFigure 1 Figure 2 .